Quality schemes and pastoralism in France - Claire Aubron; Marceline Peglion; Marie-Odile Nozières; Jean-Pierre Boutonnet (Revue de Géographie Alpine)
Strengthening and securing economic activity in rural areas figure among the objectives of French policy on the quality and origin of agricultural products. This is particular true for territories known for their harsh terrain. In mountainous Mediterranean hinterland regions, numerous quality schemes have been developed which rely in a more or less explicit manner on pastoralism. This article focuses on the relationship, made of synergies and paradoxes, between quality schemes and pastoralism in France. To do so, we build on an understanding of the dynamics and diversity of farms in 5 areas of the Mediterranean hinterland where 8 official quality labels are subject to certification. An analysis of the specifications of these quality schemes suggests that while they contribute to the recognition of pastoral livestock farming practices, they also tend to constrain them. To better respond to downstream demands, the schemes make choices regarding volumes and the seasonality of production that sometimes are inconsistent with pastoralism. Furthermore, while they undeniably contribute to territorial development, increases in the size and level of equipment of farms engaged in quality schemes are jeopardizing their genuinely pastoral character.